Cryptographic hardware and embedded systems -- CHES 2015 : 17th International Workshop, Saint-Malo, France, September 13-16, 2015, Proceedings /: 17th International Workshop, Saint-Malo, France, September 13-16, 2015, Proceedings. (2015) - Unknown
No abstract available